Bioentrepreunership for orphanages by making kokedama and capillary system plant cultivation - Hasanah, Yaya (Talenta Publisher Universitas Sumatera Utara, 2021)
Bumi Nusantara Medan Orphanage is an orphanage located in Medan Sunggal District, Medan City. The location of the orphanage is quite close to the location of shops, schools and residential areas, so it is very strategic to be developed into a place of business considering that access to markets and buyers is very close. The purpose of this community service is to increase the empowerment of the orphanage community through urban farming-based bioentrepreneurship by making kokedama and capillary system plant cultivation, so that it becomes a business opportunity that can improve the welfare of the orphanage. The implementation method that will be carried out to solve this problem is through introduction, training and manufacture of kokedama and capillary system plant cultivation accompanied by direct practice and mentoring, and business management training. The results of the service that have been achieved are training and assistance in making kokedama and capillary system cultivation, training and hands-on practice on how to make kokedama, training and direct practice, namely training and mentoring in making kokedama and capillary system cultivation.